2005
DOI: 10.1136/bmj.38441.429618.8f
|View full text |Cite
|
Sign up to set email alerts
|

Surgical stabilisation of the spine compared with a programme of intensive rehabilitation for the management of patients with chronic low back pain: cost utility analysis based on a randomised controlled trial

Abstract: Objective To determine whether, from a health provider and patient perspective, surgical stabilisation of the spine is cost effective when compared with an intensive programme of rehabilitation in patients with chronic low back pain. Design Economic evaluation alongside a pragmatic randomised controlled trial. Setting Secondary care. Participants 349 patients randomised to surgery (n = 176) or to an intensive rehabilitation programme (n = 173) from 15 centres across the United Kingdom between June 1996 and Feb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
144
0
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(153 citation statements)
references
References 19 publications
2
144
0
7
Order By: Relevance
“…[16,27,28,46,59,61,62,76], and also as outcome instrument in National Quality Registers of spine surgery, e.g. [38,64,65].…”
Section: Preference-based Health Profile Instrumentsmentioning
confidence: 99%
“…[16,27,28,46,59,61,62,76], and also as outcome instrument in National Quality Registers of spine surgery, e.g. [38,64,65].…”
Section: Preference-based Health Profile Instrumentsmentioning
confidence: 99%
“…In evaluations of multimodal intervention procedures, a common valuation of this direct cost is often conceptualized as the hours or units of treatment billed (Critchley, Ratcliffe, Noonan, Jones, & Hurley, 2007;Hatten, Gatchel, Polatin, & Stowell, 2006;Rivero-Arias et al, 2005;Rivero-Arias, Gray, Frost, Lamb, & Stewart-Brown, 2006). Non-medical costs involve direct costs consequent to the intervention, but otherwise not classified under any type of medical modality.…”
Section: Valuation Of Costsmentioning
confidence: 99%
“…Although the majority of CEA and CUA evaluations on non-malignant pain and disability focus on interventions for spinal disorders (e.g., Hatten, Gatchel, Polatin, & Stowell, 2006;Rivero-Arias et al, 2005;Rivero-Arias, Gray, Frost, Lamb, & StewartBrown, 2006), economic evaluations on other related fields of medical research have also been reported, including biopyschosocial treatments for temporomandibular disorders (Stowell, Gatchel, & Wildenstein, 2007), workplace interventions for psychiatric patients (van Oostrom et al, 2008), and acute and subacute pain interventions in primary or secondary care facilities Karjalainen et al, 2004).…”
Section: Cost-effectiveness Of Biopsychosocial Pain Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four out of five individuals experience an episode of acute LBP at least once in their lifetime, and about 5% develop chronic LBP, which is defined as LBP lasting longer than 12 weeks [50]. The economic cost of treating patients with chronic LBP exceeds that of treating those with acute LBP by a significant amount leading to a high economic burden when treating spinal disorders [17,39].…”
Section: Introductionmentioning
confidence: 99%